Karakteristik Termal Material Komposit Berbahan Dasar Polipropilena dan Batang Pisang - Tajalla, Gusti Umindya Nur; Andriansyah, Prisky; Riyadi, Ilham Tri; Vadila, Mei Lisa Nur; Laksono, Andromeda Dwi (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
Thermal insulation in a residence can help keep the room's temperature stable, allowing maximum comfort at work and relaxation. Because of its low thermal conductivity value of 0.1166 W/mK, banana stem fiber (BP) is an environmentally friendly thermal insulation material, while the matrix uses polypropylene (PP). Because excessive polypropylene production can pollute the environment, recycled polypropylene (PPDU) should be investigated as a candidate matrix. This study employs compression molding at a pressure of 8 MPa and a temperature of 170 °C for 60 minutes, with volume fractions of banana stem fibers varying by 10%, 30%, and 50%, as well as different matrix types, namely PP and PPDU. The manufacturing results were then evaluated using density and thermal conductivity tests. The density testing results for BP/PP and BP/PPDU decreased as more volume fractions were added. This phenomenon can occur as a result of void formation during the manufacturing process. Furthermore, the thermal conductivity values for BP/PP increased from 0.37 to 0.89 W/mK and from 0.58 to 0.94 W/mK for BP/PPDU, respectively. The lower the thermal conductivity value, the smaller the volume fraction of fiber. Similarly, pure PP is preferable because it has lower conductivity values than PPDU.